Teaching with Moodle in higher education - Lopes, Ana Paula (2012)
Nowadays, with the use of technology and the Internet, education is undergoing significant changes, contemplating new ways of teaching and learning. One of the widely methods of teaching used to promote knowledge, consists in the use of virtual environments available in various formats, taking as example the teaching-learning platforms, which are available online. The Internet access and use of Laptops have created the technological conditions for teachers and students can benefit from the diversity of online information, communication, collaboration and sharing with others. The integration of Internet services in the teaching practices can provide thematic, social and digital enrichment for the agents involved. In this paper we will talk about the advantages of LMS (Learning Management Systems) such as Moodle, to support the presential lectures in higher education. We also will analyse its implications for student support and online interaction, leading educational agents to a mixing of different learning environments, where they can combine face-to-face instruction with computer-mediated instruction, blended-learning, and increases the options for better quality and quantity of human interaction in a learning environment. We also will present some tools traditionally used in online assessment and that are part of the functionalities of Moodle. These tools can provide interesting alternatives to promote a more significant learning and contribute to the development of flexible and customized models of an evaluation which we want to be more efficient.